A finite element analysis of residual stress in brazing of sapphire and inconel / Chan Chow Khuen - Chan, Chow Khuen (2011)
A research cum study project has been done on the finite element analysis of residual stress in brazing sapphire and Inconel. The Inconel covered in this research study is Inconel 600. The materials used in this research project are sapphire, Inconel 600, brazing filler BAg-8-Ti, copper and nickel. The sample model is modelled in Ansys Mechanical APDL simulation software. In this the simulation, the thermal mechanical analysis is performed. In this thermal mechanical analysis, there are two main categories of simulation, which are transient thermal analysis and thermalstructural analysis. In the transient thermal analysis, the heat conduction between interlayer is discovered and studied. Subsequently, the thermal-structural analysis is performed in order to obtain the Von Mises stress distribution. The stress distribution is then compared with the yield strength of each type of material used. The stress which exceeds the yield strength is the cause of residual stress. In this research project, it is discovered that sample 3 with brazing temperature 8650C is the optimum parameter as it has less residual stress impact.